Caracterização do vírus da síndrome da mancha branca (WSSV) prevalente no período de 2012, 2016 e 2018 no Município de Aracati (CE) - Siqueira, Ingrid Luana da Silveira (2019)
In the past twenty years, marine shrimp farming have expanded rapidly around the world. With this expansion came the emergence and dissemination of a number of shrimp diseases. Among the main pathogens, White Spot Syndrome Virus (WSSV) is possibly the most severe and the most persistent through the years. White spot disease is well known today. However, considerably less is known about WSSV origin, evolution and variation. In Brazil, the state of Ceará is one of the largest shrimp producers in Brazil. WSSV has been present in the state since 2005, significantly affecting production in 2016. Considering this background, the objective of the present work was to detect WSSV genotypic variants in cultured Litopenaeus vannamei shrimp, during 2012, 2016 and 2018, in the municipality of Aracati (CE). Through this approach, this work seeks to improve the knowledge about WSSV epidemiology, propagation and dynamics. The presence of WSSV was evaluated by histological analysis and quantitative real time PCR (qPCR). The analysis and characterization of the viral strains present were performed through analysis of the ORFs 75, 94 and 125 and the VRs 14/15 and 23/24. The results showed that the samples evaluated for the years 2012, 2016 and 2018 presented, respectively, a prevalence of 22.4%, 95% and 46.7% for WSSV, with an average viral load of 1,3 x 102, 7.34 x 107 e 1.72 x 104 virus copies per μg DNA. The analysis of minisatellites indicated the presence of 68 viral genotypes. These results suggest that the severity of WSSV outbreaks in the region are likely linked not only to the virus presence, but also to the presence of different viral strains and their interactions.